On regret: A sociological intersectional approach - D'Avelar, M. M. (2022)
Regret is more than just an individual cognitive and emotional phenomenon, and it can, and should, be seen as social and cultural as well. Because of this, regret can tell us a lot, both about someone’s biography, and about the society and culture that shape it. In this brief reflection, the aim is to look at regret as a phenomenon worthy of sociological focus. We focus on three main ways in which regret can be understood as a sociological object: regret as a part of someone’s biography, regret as something that is culturally shaped, and regret as a part of collective memory. We also explore the potentialities of using an intersectional framework to analyze regret in its different forms.